Textbook for orthodontic therapists - Davies, Ceri (Hoboken, NJ : Wiley Blackwell, 2020)
'Textbook for Orthodontic Therapists is a comprehensive text specifically designed for orthodontic therapists. Written in an accessible and digestible format, it provides the essential clinical and theoretical knowledge needed for daily clinical practice. Covering learning outcomes required by the examining bodies and the General Dental Council (GDC), it includes topics such as common types of orthodontic appliances, frequently found orthodontic problems, skeletal assessment and classification of malocclusion. It also contains information on subjects relevant to the dental profession for example medical emergencies, clinical governance and more. Written to help the reader understand the role and function of an orthodontic therapist, Textbook for Orthodontic Therapists offers support to those undertaking the Diploma in Orthodontic Therapy and to assist those who already work as orthodontic therapists, helping them in their quest to enhance safe and effective care'--
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Orthodontics -- Methods; Tooth Diseases -- Therapy; Orthodontic Appliances